Curious Legal Conditionals - Berezowski, Leszek (Research in Language, 2011)
The paper examines the use of the modal verb SHALL in the if clauses of conditionals found in legal English. The study traces the history of such usages and compares them to two uses of WILL attested in the same grammatical environment: a temporal use and a nonepistemic modal use. The comparison provides the foundation for examining the use of SHALL in Biblical translations, where this verb has outlived its demise in general English, and both of these sources inform the analysis of SHALL in legal conditionals. Specifically, it is claimed that SHALL is not inherently deontic in legal English but is used as an explicit marker of the authority vested in the author or authors of spoken and written texts. This approach explains why authority conscious drafters can use SHALL in the if clauses of conditionals and in temporal clauses whenever they want to and why the proponents of the plain language movement advocate simply deleting SHALL from legal writing and not replacing it with more popular modals expressing deontic meanings, e.g. HAVE TO, MUST, etc. It is claimed that no such replacements are recommended because there is no deontic meaning to replace and the authority designated by SHALL can be inferred from the context.